BAHAYA SAMPAH PLASTIK DI LAUT BAGI MAHLUK HIDUP - Muhammad Yatzin Azharil; Immanuel Paskah (Riset Sains dan Teknologi Kelautan, 2023)
Abstract Plastic pollutes our planet and harms the oceans, endangering human health and destroying ecosystems that are essential to our livelihoods. Our oceans have faced serious threats from marine debris, also known as "marine debris," which has disturbed and attracted global attention for its ecological impacts. , economical , and extensive health. The research used is descriptive in nature which aims to describe the conditions in coastal and marine areas. The problem of marine waste has a huge impact because most of the waste is plastic which is difficult to decompose. Data from the UN Ocean Conference in New York, USA in 2017 shows that plastic waste in the ocean has killed around 1 million seabirds, 100,000 marine mammals, as well as a number of fish and turtles. . Meanwhile, World Wildlife Fund Indonesia (WWF) research shows that up to 25% of marine fish species contain microplastics. This microplastic material is obtained from marine debris measuring <5 mm and consumed by plankton which is the main food source for fish in the ocean. Talking about Indonesia, data from the Indonesian Institute of Sciences (LIPI) Oceanographic Research Center (P2O) shows that every year, Indonesia's oceans are estimated to receive 70-80% of plastic waste originating from human consumer activities. toxic chemicals, some of which are found in the open ocean Keywords: sea plastic, beaches, and rubbish